Affective and situational correlates of foreign language proficiency: A study of Chinese university learners of English and Japanese - Jin, Yinxing; de Bot, Kees; Keijzer, Merel (Studies in Second Language Learning and Teaching, 2017)
The study explores the effects of teacher support and student cohesiveness on foreign language (FL) learning outcomes and compares their effect with that of FL anxiety. One hundred and forty-six first-year Chinese undergraduates of Japanese, who were also learning English, participated in two surveys that were administered over a 2-month interval. Data were collected using the Foreign Language Classroom Anxiety Scale (Horwitz, Horwitz, & Cope, 1986), the Teacher Support Scale (Trickett & Moos, 2002), the Affiliation Scale (Trickett & Moos, 2002), the English Proficiency Scale, and the Japanese Proficiency Scale. It was found that (a) student cohesiveness was a positive predictor of FL proficiency, (b) teacher support, which was positively related to student cohesiveness and negatively to FL anxiety, did not show a direct relationship with FL proficiency, and (c) FL anxiety, which was negatively associated with FL proficiency, showed a better predictive power than student cohesiveness and teacher support.